THE CHALLENGE OF PEOPLE MANAGEMENT: : DIVERSITY MANAGEMENT - Cristina Gularte Liberato, Carla (Revista Gênero e Interdisciplinaridade, 2021)
Diversity expands horizons, presents new possibilities and increases the repertoire. The corporations that are ahead with their training and inclusion of diversity initiatives have noticed increased productivity generated by the team's collaboration and synergy; in addition to flexibility resulting from living with different people. In order to get to know the topic on the rise in society today, we carried out a bibliographic review on the theme “Management of diversity” and its interfaces, definition, challenges and the role of technology in people management. We know the greatness of the theme and the difficulty of its implementation. We live in a country that was diverse since its conception, grand by nature, receptive to migrants and immigrants, but still with immense difficulties in the management of social differences.